A "Mascara Embelezada" - Arquitetura e moral iluminista - Nobre, Ana Luiza (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 1996)
This paper intends to discuss de significance, in Architecture, of the moral notion assumed by the French Enlightenment, through the investigation of the entry "Architecture", found in Diderot e D'Alembert's "Encydopédie". With this aim, it deals with the concepts of "genius" and "taste", seeking to associate them with the aesthetical idea related to eighteenth-century thought